The politics of the past in an Argentine working-class neighbourhood - DuBois, Lindsay (Anthropological horizons, 2005)
"The Argentine dictatorship of 1976 to 1983 set out to transform Argentine society. Employing every means at its disposal - including rampant violation of human rights, union busting, and regressive economic policies - the dictatorship aimed to create its own kind of order. Lindsay DuBois's The Politics of the Past explores the lasting impact of this authoritarian transformative project on the people who lived through it." "DuBois's ethnography centres on Jose Ingenieros, a Buenos Aires neighbourhood founded in a massive squatter invasion in the early 1970s, and describes how the military government's actions largely subdued a politically engaged community. DuBois traces how state repression and community militancy are remembered in Jose Ingenieros and how the tangled and ambiguous legacies of the past continued to shape ordinary people's lives years after the collapse of the military regime." "This study breaks new ground in its exploration of the complex relationships between identity, memory, class formation, neoliberalism, and state violence."--Jacket.